AKIBAT HUKUM ATAS PEMBAGIAN WARISAN BERDASARKAN SURAT KETERANGAN AHLI WARIS YANG TIDAK MENCANTUMKAN SELURUH AHLI WARIS - NURUL AINI LUBIS (PREMISE LAW JURNAL, 2017)
Inheritance Law is a part in the Civil Code in a whole and is the smallest part of the Law of Mutual Cooperation. Therefore, it is necessary to have a strict regulation which meets the elements of legal consequence in making a latter of notification of heir which is the proof of heir, either concerning the official’s authority that makes it or the procedure of making it. With the Letter of Notification of Heir, an heir can show a proof of being an heir when a problem arises related to the determination of heirs of the dead person. It is a proof so that the problem can be settled. It is a proof for the society to correctly find out who is the rightful heir for the property inherited by the dead person; thus, the heir can show the letter of notification of an heir as evidence so that the case can be solved. This letter of notification is evidence for the society to properly find out the rightful person for the inheritance which is used as the ground for its distribution to the rightful person and/ or how much the part belonging to the heir either according to the legitimate portie or the will. Keywords: Inheritance, Heir, Notification latter of heir